Dynamic response of water flow and sediment transport off the Yellow River mouth to tides and waves in winter - Cheng, Xinyue; Zhu, Jianrong; Chen, Shenliang (Frontiers in Marine Science, 2023)
The fresh water and sediments are transported from the Yellow River mouth downstream along the coast into the Laizhou Bay under the northeasterly wind in winter. The sediment transport shows the tendency of convergence in the river mouth, divergence in the downstream area, and convergence in the north of Laizhou Bay. Tides and waves are the two main forcings affecting the transport of water and sediments off river mouths. For the high-turbidity Yellow River mouth and the adjacent sea, tidal forcing enhances the subtidal downstream transport of water and sediments off the river mouth into the Laizhou Bay, whereas wave forcing has little effect on the advection of water and sediments. The sediment resuspension is controlled by the bottom shear stress induced by tides and waves. The tide-induced bottom shear stress is higher in the north of Laizhou Bay and south of Bohai Bay due to the stronger bottom tidal current. The wave-induced bottom shear stress plays a more important role in sediment resuspension, which is higher in the nearshore region along the Yellow River Delta away from the coast to some extent on account of the maximum near-bottom wave orbital velocity. Tidal mixing strengthens the upward diffusion of bottom suspended sediments. Without tidal forcing, there is an interesting phenomenon along the Yellow River Delta. In the nearshore region, the decreased bottom shear stress suspends less sediment above the bed. However, in the offshore region, the enhanced stratification hinders the upward diffusion of the bottom sediment due to the lack of tidal mixing, resulting in higher suspended sediment concentration (SSC) in the bottom layer.